Mineralocorticoid and AT1 receptors in the paraventricular nucleus contribute to sympathetic hyperactivity and cardiac dysfunction in rats post myocardial infarct. (14th July 2014) - Huang, Bing S.; Chen, Aidong; Ahmad, Monir; Wang, Hong‐Wei; Leenen, Frans H. H.
<x xml:space="preserve">Abstract</x> Key points Central mineralocorticoid receptor (MR) and angiotensin II type 1 receptor (AT1R) activation play a critical role in sympathetic hyperactivity and progressive left ventricle (LV) remodelling and dysfunction after a myocardial infarction (MI). Intra‐paraventricular nucleus (PVN) infusion of adeno‐associated virus (AAV) carrying small interfering RNA (siRNA) against MR (AAV‐MR‐siRNA) markedly decreases both MR and AT1R expression in the PVN post MI, whereas AAV‐AT1aR‐siRNA only decreases AT1R expression. Both AAVs largely prevent sympathetic hyperactivity and inhibit part of LV remodelling and dysfunction post MI. These findings indicate that enhanced MR–AT1R signalling in the PVN is critical for sympathetic hyperactivity post MI, and contributes to part of LV dysfunction post MI. Abstract Intracerebroventricular infusion of a mineralocorticoid receptor (MR) or angiotensin II type 1 receptor (AT1R) blocker in rats attenuates sympathetic hyperactivity and progressive left ventricular (LV) dysfunction post myocardial infarction (MI). The present study examined whether knockdown of MRs or AT1Rs specifically in the paraventricular nucleus (PVN) contributes to these effects, and compared cardiac effects with those of systemic treatment with the β1‐adrenergic receptor blocker metoprolol. The PVN of rats was infused with adeno‐associated virus carrying small interfering RNA against either MR (AAV‐MR‐siRNA) or AT1R (AAV‐AT1R‐siRNA), or as control scrambled siRNA. At 4 weeks post MI, AT1R but not MR expression was increased in the PVN, excitatory renal sympathetic nerve activity and pressor responses to air stress were enhanced, and arterial baroreflex function was impaired; LV end‐diastolic pressure (LVEDP) was increased and LV peak systolic pressure (LVPSP), ejection fraction (EF) and dP/dtmax decreased. AAV‐MR‐siRNA and AAV‐AT1R‐siRNA both normalized AT1R expression in the PVN, similarly ameliorated sympathetic and pressor responses to air stress, largely prevented baroreflex desensitization, and improved LVEDP, EF and dP/dtmax as well as cardiac interstitial (but not perivascular) fibrosis. In a second set of rats, metoprolol at 70 or 250 mg kg−1 day−1 in the drinking water for 4 weeks post MI did not improve LV function except for a decrease in LVEDP at the lower dose. These results suggest that in rats MR‐dependent upregulation of AT1Rs in the PVN contributes to sympathetic hyperactivity, and LV dysfunction and remodelling post MI. In rats, normalizing MR–AT1R signalling in the PVN is a more effective strategy to improve LV dysfunction post MI than systemic β1 blockade.